Exploring Students’ Perceptions of Literary Translation through ChatGPT: A Case Study at the Faculty of Languages and Translation, University of Zawia, Libya - Mahmoud Abdullah; Khuloud Alouzi; DafaAllah Ibrahim; Mowafg Masuwd; Hajer Albshkar (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
This study investigates students’ experiences and attitudes towards the use of artificial intelligence (AI) tools in literary translation at the Faculty of Languages and Translation, University of Zawia, Libya. Sixty undergraduate students from English departments participated in a classroom-based experiment in which they translated literary texts using ChatGPT. Following the translation tasks, students completed a structured questionnaire designed to assess the usability, accuracy, and pedagogical value of AI-assisted translation. Descriptive analysis of the data revealed that while students found AI-tools effective for increasing translation speed and acquiring new vocabulary, they also expressed reservations about the tools’ limitations in handling literary devices such as tone, metaphor, and cultural context. A majority of students are in favor of continued use of AI-tools under instructor guidance, recognizing their value as supplementary learning aids rather than replacements for human translators. The study highlights the need for critical integration of AI into translation pedagogy and encourages further research on balancing automation with interpretive and creative human input.